Case report: Endoscopic retrieval of a proximally migrated pancreatic stent using the basket-through- the-sphincterotome technique - Yi, Hang; Liu, Qin; He, Song; Zhong, Li; Guo, Xiaodong; Wu, Suhua; Ning, Bo (Frontiers in Medicine, 2023)
Abstract Background: The retrieval of a proximally migrated pancreatic duct (PD) stent via endoscopic retrograde cholangiopancreatography (ERCP) is technically challenging, often requiring surgical intervention. We report a case with proximal migration of a pancreatic stent that was successfully removed by a basket-through-the-sphincterotome technique. Case presentation: A 46-year-old man with prior history of chronic pancreatitis was admitted to our hospital with one month history of epigastric discomfort. Nine months prior he had undergone ERCP with Endoscopic sphincterotomy (EST) and a 5 Fr×9 cm plastic pancreatic stent placement to relieve pancreatic duct stricture and abdominal pain. Magnetic retrograde cholangiopancreatography (MRCP) done this time revealed PD dilation and a stent-shaped signal inside the PD. The subsequent endoscopic ultrasonography (EUS) verified total pancreatic stent proximal migration with no visible distal end of the stent in the papilla. ERCP was performed again with an attempt to retrieve the stent. General techniques of PD cannulation with a 0.035-inch guidewire over the migrated stent and balloon extraction failed. We used a mini-basket (Endoflex Germany) to replace the guidewire, which was inserted into the PD and advanced over the proximal end of the stent through the channel of the sphincterotome. The distal end of the stent was easily caught by manipulating the tip of the sphincterotome, and the stent was then pulled out. A naso-pancreatic drainage tube was placed in the main PD, and the patient was discharged two days after tube withdrawal. Conclusions: This was a successful case of proximally migrated pancreatic stent retrieval using the unique idea of basket-through-the-sphincterotome technique, which has rarely been reported. The basket-through-the-sphincterotome technique provides the endoscopist another way to catch the distal end without difficulty. It can improve the success rate of proximally migrated pancreatic stent retrieval, especially the pig-tail pancreatic stent, of which the sticking of the proximal end into pancreatic duct branches often makes the distal end the only choice to retrieve.